2004
DOI: 10.1096/fj.03-1212fje
|View full text |Cite
|
Sign up to set email alerts
|

Targeting kallikrein 6‐proteolysis attenuates CNS inflammatory disease

Abstract: Kallikrein 6 (K6, MSP) is a newly identified member of the Kallikrein family of serine proteases that is preferentially expressed in the adult central nervous system (CNS). We have previously demonstrated that K6 is abundantly expressed by inflammatory cells at sites of CNS inflammation and demyelination in animal models of multiple sclerosis (MS) and in human MS lesions. To test the hypothesis that this novel enzyme is a mediator of pathogenesis in CNS inflammatory disease, we have evaluated whether autonomou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
134
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(138 citation statements)
references
References 49 publications
3
134
0
1
Order By: Relevance
“…The most clearly established causes of ER stress- induced apoptosis involve protein mutations leading to protein misfolding, for example, the missense mutation in insulin 2 in the Akita mouse (35) and peripheral neuropathy as a result of mutations in the P0 protein (36). High expression rates of human IAPP in mice leads to the formation of toxic intracellular IAPP oligomers (37), implying misfolding and/or intracellular trafficking of human IAPP beyond a critical threshold of expression.…”
Section: Fig 5 Expression Of Perinuclear Chop and Insulin In Human mentioning
confidence: 99%
“…The most clearly established causes of ER stress- induced apoptosis involve protein mutations leading to protein misfolding, for example, the missense mutation in insulin 2 in the Akita mouse (35) and peripheral neuropathy as a result of mutations in the P0 protein (36). High expression rates of human IAPP in mice leads to the formation of toxic intracellular IAPP oligomers (37), implying misfolding and/or intracellular trafficking of human IAPP beyond a critical threshold of expression.…”
Section: Fig 5 Expression Of Perinuclear Chop and Insulin In Human mentioning
confidence: 99%
“…Additionally, while not fully elucidated, kallikreins likely participate in activation/inactivation cascades with other serine proteases [25] and, indeed, may be regulated by overlapping endogenous inhibitors such as α1-antichymotrypsin, α1-antitrypsin, and α2-macroglobulin [157]. Already, kallikrein 6 (K6), the most abundant kallikrein in CNS with preferential expression by neurons and oligodendroglia, has been shown to be upregulated at sites of active demyelination in MS lesions, in TMEV, and in EAE models [26,27,45,229]. Importantly, inhibiting K6 enzymatic activity delays the onset of disease and reduces clinical and histological signs in EAE.…”
Section: Tissuementioning
confidence: 99%
“…Importantly, inhibiting K6 enzymatic activity delays the onset of disease and reduces clinical and histological signs in EAE. Notably, disease attenuation parallels diminished Th1 responses, which points to a prominent role for K6 not only in lesion development but also in modulation of the inflammatory response [27]. Furthermore, it was recently demonstrated that kallikreins are not only capable of modifying the extracellular environment but, like other serine proteases, may serve in a hormone-like capacity by virtue of their ability to activate select PAR.…”
Section: Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…For example, hK5, -6, and -14 are found at increased levels in the serum and/or ascites fluid of ovarian cancer patients (22)(23)(24)(25)(26) as well as in the serum of breast cancer patients (23,26). Kallikreins are also highly expressed at sites of inflammation (27,28). However, despite their widespread expression in diseased tissues, the mechanisms whereby this enzyme family regulates cellular function are not clear.…”
mentioning
confidence: 99%